Central bank communication and trust: An experimental study on the European Central Bank and the general public - Sarah Mochhoury (European Central Bank (ECB), 2023)
While it has become clear that communication is a monetary policy tool for central banks, and extensive research has been conducted on central bank communication with financial markets, little is known so far on central bank communication with the general public. My research provides new insights into this field, confirming that the efforts of central banks to connect with a wider public are not in vain. In a randomised controlled trial, I focus on the determinants of trust in the European Central Bank (ECB) and on understanding of its communication about the Pandemic Emergency Purchase Programme, which was set up as part of the ECB's response to the COVID-19 crisis. I find that the ECB's simplified and relatable communication leads to greater trust in the central bank among the general public, as it has a positive impact on perceptions of the ECB among laypeople. The simplified content also proves to contribute to increased understanding of the central bank's messages among the wider public.
Keywords: C83; C93; D83; E52; E58; 330; Central bank communication; Trust; Behavioural economics; Experimental economics; European Central Bank